The Effect Of Post-Tensioned Steel on A Girder Structure - Mohd Rozali, Muhammad Haniffudin (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study investigates the flexural behavior of bonded post-tensioned (BPT) reinforced concrete cantilever girders with different tendon profiles. The girders are analyzed using the finite element (FE) approach with the ANSYS software. Experimental tests are conducted to validate the FE analysis, and the results show satisfactory agreement. The six models considered in the study include configurations with no tendons, two tendons in the middle, two draped points on parabolic tendons at the bottom, and no tendons at the top. The evaluation includes analyzing failure loads, deflections, and load-deflection relationships. The findings indicate that the girder with a single draped tendon profile exhibits the best performance. Overall, prestressing is an effective and cost-efficient technique for enhancing the strength and minimizing deflections in reinforced concrete structures..